PENGARUH INTENSITAS PENGGUNAAN GENERATIVE ARTIFICIAL INTELLIGENCE TERHADAP BERPIKIR KRITIS DAN HASIL BELAJAR MAHASISWA - Prasetya Yoga Santoso; Ressa Uli Patrissia (LPMP Provinsi DKI Jakarta, 2026)
This study examines the effect of Generative Artificial Intelligence (Gen AI) usage on the critical thinking skills and learning outcomes of university students in Indonesia. The novelty of this research lies in the integration of AI literacy as a moderating variable, which has not been studied simultaneously in the context of Indonesian higher education. The study employed a one-shot case study pre-experimental method with 50 students as samples, divided into three groups based on Gen AI usage intensity: low (n=16), moderate (n=17), and high (n=17). Data were analyzed using one-way Analysis of Variance (ANOVA). Results revealed significant differences in critical thinking skills (F(2,47) = 18.43, p < .001) and learning outcomes (F(2,47) = 22.17, p < .001) among the three groups. The high-intensity Gen AI group obtained the highest mean critical thinking score (M = 84.71, SD = 5.34) and the best learning outcomes (M = 87.12, SD = 4.91). This study recommends structured integration of Gen AI into higher education curricula accompanied by enhanced AI literacy for students.